Plan de negocio para la creación de una empresa productora y comercializadora de zapatos de futbol, en el cantón Quinsaloma año 2014. - Cajas Iza, Edwin Javier (2015)
This project involves the development of a business plan for starting a business producer and marketer of soccer shoes in Canton Quinsaloma. For this project, market research was conducted to identify which are the internal and external factors that can affect the success of the company, in which it was determined that there is a favorable environment for the creation of producer and marketer of soccer shoes limited acceptance in the local market and competition. The company's name 3Q SPORT, Company Producer and marketer of soccer shoes will be located on Avenida Pangua between Calle Simon Bolivar and Zoilo Franco just meters from the center of the county, this being a strategic location to launch the company….